SISTEM PENCATATAN, PELAPORAN, PENGANGGARAN DAN PENGENDALIAN DALAM PENGELOAAN KEUANGAN BISNIS UMKM KECAMATAN KARTOSURO - Evi Dewi Kusumawati (STIE St. Pignatelli Surakarta, 2021)
The purpose of this suty is to determine the financial management applied at Small Medium Enterproses (SME) at Kecamatan Kartosuro. This research was a case study, the data collected from the member Small Medium Enterprises at Kecamatan Kartosuro by distributing quesionaries and interview. The data was analysed by descriptive qualitative analysis. The result showed that SME at Kecamatan Kartosuro have implemented the financial management especially recorded and budgeting, but most of SME less to implemented in making Financial Report, because of they don’t have accounting knowledge.